A 3-Arm randomised controlled trial of Communicating Healthy Beginnings Advice by Telephone (CHAT) to mothers with infants to prevent childhood obesity. (December 2017) - Wen, Li; Rissel, Chris; Baur, Louise; Hayes, Alison; Xu, Huilan; Whelan, Anna; Hua, Myna; Shaw, Miranda; Phongsavan, Philayrath
Abstract Background With an increasing prevalence of obesity in young children globally, there is an urgent need for the development of effective early interventions. A previous Healthy Beginnings Trial using a nurse-led home visiting program has demonstrated that providing mothers with evidence-based advice can improve maternal practice regarding obesity prevention, and can reduce Body Mass Index (BMI) in the first few years of life. However, the costs for scale-up of home visiting limit its population reach. This trial aims to determine the efficacy of Communicating Healthy Beginnings Advice by Telephone (CHAT) to mothers with infants in improving infant feeding practices and preventing the early onset of childhood overweight and obesity. Methods/Design We propose a 3-arm randomised controlled trial (RCT) with a consecutive sample of 1056 mothers with their newborn children in New South Wales (NSW) Australia. Pregnant women who are between weeks 28 and 34 of their pregnancy will be invited to participate in the CHAT trial. Informed consent will be obtained, and after baseline data collection, participants will be randomly allocated to the telephone intervention, text messaging intervention, or the control group. The intervention comprises telephone consultations or text messages, together with 6 intervention packages being mailed at specific times from the third trimester of pregnancy until 12 months post birth. The main trial outcome measures include a) duration of breastfeeding, b) timing of introduction of solids, c) nutrition behaviours, physical activity and television viewing, and d) weight and BMI z-score at 12 and 24 months, e) cost-effectiveness, as well as f) feasibility and acceptability of the interventions. Discussion The results will ascertain whether early intervention using telephone consultation or text messaging together with staged mailed intervention resources can be feasible and effective in improving infant feeding practices, physical activity and reducing children's BMI in the early years of life. If proven to be feasible, effective as well as cost-effective, the trial results will inform a series of recommendations for policy and practice related to promoting healthy infant feeding and physical activity in young children in the first years of life. Trial registration The CHAT Trial is registered with the Australian Clinical Trial Registry (ACTRN12616001470482p ). It was registered on October 21, 2016.